Internalisasi Nilai-nilai Pendidikan Agama Islam Dalam Pembelajaran Berbasis Sentra di Taman Kanak-kanak Islam Terpadu Al-Hijrah Bintuju Kabupaten Tapanuli Selatan - Maisaroh Maisaroh (Studi Multidisipliner: Jurnal Kajian Keislaman, 2018)
This study aims to describe internalizing values of Islamic Religious Education in learning based centre. This research is classified into qualitative research. Data collection instruments used were observation, interviews and document study. Data analysis used is descriptive qualitative analysis. From the research carried out, the results were obtained, namely: 1. The values of Islamic Religious Education internalized in the center of al-Islam are three, namely: a. Faith value b. Value of worship. c. Moral values. Internalization method: Lecture, question and answer, habituation, exemplary, advice, attention and supervision and story. 2. The values of Islamic Religious Education that are internalized in a language center are three, namely: a. Faith value. b. Value of worship. c. Moral values. 3. There are three values that are internalized in the cognitive center, namely: a. value of faith. b. value of worship. c. Moral values. 4. The values internalized in the center of science are the values of aqeed and morals.